2016
DOI: 10.1111/1755-5922.12235
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of two dosages of canrenone as add‐on therapy in hypertensive patients taking ace‐inhibitors or angiotensin II receptor blockers and hydrochlorothiazide at maximum dosage in a randomized clinical trial: The ESCAPEIT trial

Abstract: Summary Aim To evaluate the effects of canrenone as add‐on therapy in patients already treated with angiotensin‐converting enzyme inhibitors ( ACE ‐I) or angiotensin II receptor blockers ( ARB s) and hydrochlorothiazide at the maximum dosage (25 mg/d). Method In this randomized, open‐label, controlled trial, we enrolled 175 Caucasian patients with essential hypertension not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… 6 The effects of canrenone on BP were already previously reported in two previous papers where the authors reported that the systolic and diastolic BP (24 h, daytime and nighttime) and mean arterial and pulse pressures were significantly reduced when canrenone was added to the preexisting therapy. 10 , 11 Moreover, the authors did not observe any significant differences between canrenone 50 and 100 mg: among patients treated with canrenone 50 mg, 67.5% and 74% normalized the 24 h systolic and diastolic BP, respectively, and among patients treated with 100 mg, 61.6% and 68.5% ( p not significant for 50 vs 100 mg). 10 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 6 The effects of canrenone on BP were already previously reported in two previous papers where the authors reported that the systolic and diastolic BP (24 h, daytime and nighttime) and mean arterial and pulse pressures were significantly reduced when canrenone was added to the preexisting therapy. 10 , 11 Moreover, the authors did not observe any significant differences between canrenone 50 and 100 mg: among patients treated with canrenone 50 mg, 67.5% and 74% normalized the 24 h systolic and diastolic BP, respectively, and among patients treated with 100 mg, 61.6% and 68.5% ( p not significant for 50 vs 100 mg). 10 …”
Section: Discussionmentioning
confidence: 84%
“… 10 , 11 Moreover, the authors did not observe any significant differences between canrenone 50 and 100 mg: among patients treated with canrenone 50 mg, 67.5% and 74% normalized the 24 h systolic and diastolic BP, respectively, and among patients treated with 100 mg, 61.6% and 68.5% ( p not significant for 50 vs 100 mg). 10 …”
Section: Discussionmentioning
confidence: 84%
“…As already reported for the whole population, we did not observe clinically relevant side effects in the group of patients undergoing ABPM, and in particular, no threatening hypotension episodes were seen during the 24 h BP monitoring. 24 This may be due in part to patient selection, including those patients who were already tolerant of ACE or AT1R blockade in terms of renal perfusion. As expected based on previously published literature, an increase in serum K was observed in conjunction with a non-clinically relevant increase in serum creatinine at the higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed study design has been described previously. 24 This study presents a secondary analysis focused on ABPM. Besides ABPM, all patients had a complete clinical evaluation, office visit BP measurements, and routine laboratory examinations at baseline (pre-study canrenone addition) and 3 months after canrenone addition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation